Detección precoz de hipoacusia en recién nacidos del Hospital Teófilo Dávila durante el período de marzo hasta septiembre del 2012. - Medina Morán, Yessica P. (2013)
This is a descriptive study for early detection of hearing loss in newborns in the Hospital Teofilo Davila March to September 2012, using a population of 734 newborns. Results: Of 734 infants who underwent neonatal screening 105 (14.3%) had risk factors of all newborns with risk factors 50 (47.6%) are female sex and 55 (52.4%) were male.